2017
DOI: 10.1002/cncr.31157
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of early radiologic response to induction chemotherapy in pediatric rhabdomyosarcoma: A report from the International Society of Pediatric Oncology Malignant Mesenchymal Tumor 95 study

Abstract: No evidence was found for the idea that early radiologic response to chemotherapy is prognostic for survival for patients with RMS. Treatment adaptation based on early response (except for patients with PD) should, therefore, no longer be incorporated into future studies. Cancer 2018;124:1016-24. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 32 publications
2
41
0
Order By: Relevance
“…This treatment philosophy assumes that initial response to therapy is associated with ultimate outcome and can identify chemotherapy‐sensitive tumors more likely to be cured with systemic therapy. However, recent results from MMT‐95 found that there was no correlation between early radiographic response and outcome . Two COG studies also did not demonstrate any correlation between early response and outcomes …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This treatment philosophy assumes that initial response to therapy is associated with ultimate outcome and can identify chemotherapy‐sensitive tumors more likely to be cured with systemic therapy. However, recent results from MMT‐95 found that there was no correlation between early radiographic response and outcome . Two COG studies also did not demonstrate any correlation between early response and outcomes …”
Section: Introductionmentioning
confidence: 94%
“…However, recent results from MMT-95 found that there was no correlation between early radiographic response and outcome. 9 Two COG studies also did not demonstrate any correlation between early response and outcomes. 3,5 Local control for the majority of patients with Group III RMS is achieved by definitive radiotherapy (RT) since PM-RMS tumors are usually not amenable to resection, and residual tumor masses often remain after induction chemotherapy.…”
Section: Introductionmentioning
confidence: 95%
“…Within the European paediatric soft-tissue sarcoma group, several recent retrospective studies have evaluated the impact of imaging findings on patient care, using rhabdomyosarcoma patients as the example group. One study showed that early radiologic response to chemotherapy (volumetric tumour reduction) did not infer a survival advantage in patients with rhabdomyosarcoma [34]. Another study showed that indeterminate lung nodules should be treated as non-metastatic in otherwise non-metastatic patients in rhabdomyosarcoma [35] and other studies have sought to evaluate the role of follow-up imaging [3638].…”
Section: Overarching Strategymentioning
confidence: 99%
“…Radiographic response to treatment (as measured by change in tumor size), however, has not proven to be a reliable predictor of outcome in RMS, limiting the ability to identify patients who could benefit from more intensive or novel therapy. [17][18][19] Metabolic activity as assessed by 18 F-FDG-PET/CT (FDG-PET) has recently been shown to improve accuracy of staging in pediatric RMS. 20,21 Preliminary data from a single institution suggested that a complete metabolic response (CMR) as assessed by FDG-PET following radiation therapy for local control may predict local relapse-free survival (LRFS) in pediatric patients with Group III RMS.…”
Section: Introductionmentioning
confidence: 99%